Intellectual property and entrepreneurship - Libecap, Gary D. (Emerald, 2004)
The papers in this volume represent some of the leading work on intellectual property. They address the question of how to create incentives to develop new technologies and how to protect those technologies once developed from theft. They also ask when valuable property might be developed even under weak ownership conditions. Other papers address how firms balance the trade offs in considering costly patent litigation and they examine the antitrust implications. Although issues of intellectual property rights would seem to be ones of interest only to obscure groups of academics and lawyers, they have become topics of everyday discussion among the regular population.Alleged copyright infringements by people downloading music from the internet and accompanying threats of prosecution as well as charges of strategic patenting to harm competitors in recent high profile antitrust cases have placed intellectual property into public and political debate. The incentives provided by secure property rights for promoting research and development, investment, production, and exchange are well known. These are the major arguments for patents, copyrights and other forms of intellectual property.
Keywords: Business & Economics -- Entrepreneurship.; Science -- General.; Intellectual property law.; USA.; Entrepreneurship.; Intellectual property.; elektronické knihy; electronic books